Asymptotic stabilization for switched affine systems with time delay: A novel dynamic event‐triggered mechanism. (20th October 2022) - Xie, Hongzhen; Zong, Guangdeng; Yang, Dong; Chen, Yunjun; Shi, Kaibo
Abstract: This article concentrates on the asymptotic stabilization problem of switched affine systems (SASs) with unmeasurable states and time delay by constructing a novel dynamic event‐triggered mechanism (ETM). Given the limited network transmission and the difficulties caused by affine terms in excluding the triggering Zeno behavior, we propose a novel dynamic ETM. It has been shown that the dynamic ETM not only has fewer data transfers than the existing ETM but also avoids Zeno behavior while maintaining asymptotic stability. Then, by constructing a set of dynamic output feedback switched affine controllers and switching laws, delicately incorporating Lyapunov–Krasovskii functionals, an asymptotic stabilization criterion is derived for the closed‐loop SASs. The design methods of the controllers and switching laws are skillfully implemented by solving a set of linear matrix inequalities. Finally, an application example of the flyback DC–DC converter is offered to verify the proposed algorithm.